Troubled Intimacies: Mediation and Migration in Welcome to IntelStar and The Silent Soprano - Serquiña Jr., Oscar Tantoco (Kasarinlan: Philippine Journal of Third World Studies; Vol 29 No 1 (2014): The 2014 TWSC Writeshop)
Using the plays Welcome to IntelStar and The Silent Soprano as primary materials of study, this essay looks into mediation and migration as two social phenomena that implicate national subjects who are made part of multinational/transnational spaces as call center agents and domestic helpers. It focuses on mediation and migration as tropes that serve as springboards for understanding the dialectical relationship between the  national and the global, as well as the attendant cultural, economic, and social intricacies and intimacies that this relationship engenders. Finally, it also evolves a discourse on intimacy—one that highlights affects, transformations, and power relations—from the interconnection and coexistence of the native and the foreign.